Distributed Autonomous Robotic Systems The 12th International Symposium - Chong, Nak-Young.; Cho, Young-Jo.; SpringerLink (Online service) (Tokyo : Springer Japan : Imprint: Springer, 2016)
This volume of proceedings includes 32 original contributions presented at the 12th International Symposium on Distributed Autonomous Robotic Systems (DARS 2014), held in November 2014. The selected papers in this volume are authored by leading researchers from Asia, Europe, and the Americas, thereby providing a broad coverage and perspective of the state-of-the-art technologies, algorithms, system architectures, and applications in distributed robotic systems. .
Distributed Online Patrolling with Multi-Agent Teams of Sentinels and Searchers -- Human-Robot Collaborative Topological Exploration for Search and Rescue Applications -- A Repartitioning Algorithm to Guarantee Complete, Non-overlapping Planar Coverage with Multiple Robots -- On Combining Multi-Robot Coverage and Reciprocal Collision Avoidance -- Distributed Safe Deployment of Networked Robots -- MarSim, a simulation of the MarsuBots fleet using NetLogo -- Scalable Cooperative Localization with Minimal Sensor Configuration -- Towards Cooperative Localization in Robotic Swarms -- MOARSLAM: Multiple Operator Augmented RSLAM -- Multi-Robot Manipulation without Communication -- Distributed Path Planning for Collective Transport Using Homogeneous Multi-Robot Systems -- Collective Construction of Dynamics Equilibrium Structure through the Interaction of Simple Robots with Semi-active Blocks -- Cooperative Lifting and Transport by a Group of Mobile Robots -- A Response Threshold Sigmoid Function Model forSwarm Robot Collaboration -- Potential Game-Theoretic Analysis of a Market-Based Decentralized Task Allocation Algorithm -- The Hybrid Information and Plan Consensus Algorithm with Imperfect Situational Awareness -- Adaptive Leader-Follower Formation in Cluttered Environment using Dynamic Target Reconfiguration -- A Graph-Based Formation Algorithm for Odor Plume Tracing -- Multi-agent Visibility Based Target Tracking Game -- Glider CT: Analysis and Experimental -- Validation -- Path Planning for Multi-Agent Jellyfish Removal Robot System JEROS and Experimental Tests -- Motion Planning of Multiple Mobile Robots based on Artificial Potential for Human Behavior and Robot Congestion -- DisCoF: Cooperative Pathfinding in Distributed Systems with Limited Sensing and Communication Range -- Decentralized Multi-Agent Path Selection Using Minimal Information -- Scalable Formation Control of Multi-Robot Chain Networks using a PDE Abstraction -- Decoupled formal synthesis for almost separable systems with temporal logic specifications -- Knowledge Co-creation Framework: Novel Transfer Learning Method in Heterogeneous Multi-agent Systems -- Distributed Communication and Localization Algorithms for Homogeneous Robotic Swarm -- Distributed Co-Optimisation of Throughput for Large-scale Mobile Sensor Networks -- Detection and Notification of Failures in Distributed Component-Based Robot Applications using Blackboard Architecture -- Coordination of Modular Robots by means of Topology Discovery and Leader Election: Improvement of the Locomotion Case -- Muscle Synergy Analysis of Human Standing-up Motion Using Forward Dynamic Simulation with Four Body Segment Model.
Keywords: Control engineering; Robotics; Automation; Artificial intelligence; Computational intelligence; Control, Robotics, Automation; Artificial Intelligence; Computational Intelligence